Receptor-based combinatorial nanomedicines: a new hope for cancer management - Abul Barkat, Harshita; Abul Barkat, Md; Sachi Das, Sabya; Rizwanullah, Md.; Taleuzzaman, Mohamad; Ab. Hadi, Hazrina (IGI Global, 2020)
Nanotechnology-based drug-delivery systems, as an anticancer therapy tool, have shown significant potentials for the diagnosis and treatment of cancer. Recent studies have demonstrated that cancer therapy could be efficiently achieved by combinatorial therapies, approaches using multiple drug regimens for targeting cancers. However, their usages have been limited due to shorter half-lives of chemotherapeutic agents, insignificant targetability to tumor sites and suboptimal levels of co-administered conventional drug moieties. Thus, nanotechnology-based drug-delivery systems with effective targetability have played a crucial role to overcome the limitations and challenges associated with conventional therapies and also have provided greater therapeutic efficacy. Herein, the authors have focused on various drug-incorporated combinatorial nanocarrier systems, the significance of various receptors-associated strategies, and various targeted delivery approaches for chemotherapeutic agents.